Computerised cognitive behaviour therapy for depression in adolescents: study protocol for a feasibility randomised controlled trial. Issue 10 (31st October 2014) - Wright, Barry; Tindall, Lucy; Littlewood, Elizabeth; Adamson, Joy; Allgar, Victoria; Bennett, Sophie; Gilbody, Simon; Verduyn, Chrissie; Alderson-Day, Ben; Dyson, Lisa; Trépel, Dominic; Ali, Shehzad
Abstract : Introduction: The 1 year prevalence of depression in adolescents is about 2%. Treatment with antidepressant medication is not recommended for initial treatment in young people due to concerns over high side effects, poor efficacy and addictive potential. Evidence suggests that cognitive behaviour therapy (CBT) is an effective treatment for depression and is currently one of the main treatment options recommended in adolescents. Given the affinity young people have with information technology they may be treated effectively, more widely and earlier in their illness evolution using computer-administered CBT (CCBT). Currently little is known about the clinical and resource implications of implementing CCBT within the National Health Service for adolescents with low mood/depression. We aim to establish the feasibility of running a fully powered randomised controlled trial (RCT). Methods and analysis: Adolescents aged 12–18 with low mood/depression, (scoring ≥20 on the Mood and Feelings Questionnaire (MFQ)), will be approached to participate. Consenting participants will be randomised to either a CCBT programme (Stressbusters) or accessing selected websites providing information about low mood/depression. The primary outcome measure will be the Beck Depression Inventory (BDI). Participants will also complete generic health measures (EQ5D-Y, HUI2) and resource use questionnaires to examine the feasibility of cost-effectiveness analysis. Questionnaires will be completed at baseline, 4 and 12-month follow-ups. Progress and risk will be monitored via the MFQ administered at each treatment session. The acceptability of a CCBT programme to adolescents; and the willingness of clinicians to recruit participants and of participants to be randomised, recruitment rates, attrition rates and questionnaire completion rates will be collected for feasibility analysis. We will estimate 'numbers needed' to plan a fully powered RCT of clinical and cost-effectiveness. Ethics and dissemination: The current trial protocol received a favourable ethical opinion from Leeds (West) Research and Ethics Committee. (Reference: 10/H1307/137). Trial registration number: ISRCTN31219579.